Advantages of a prospective multidisciplinary approach in transcatheter aortic valve implantation - Costa, Cátia (2017)
Copyright © 2017 Sociedade Portuguesa de Cardiologia. Publicado por Elsevier España, S.L.U. All rights reserved.